Covid 19 the life changing pandemic - Noriah Ramli, N.Ramli (The Law Brigade Publishers, 2021)
The year 2020 has witnessed the total changes in the life of many people and the Malaysian is no exception to this new normal. This new normal and compliance to Standard Operating procedure (SOP)continues till the year 2021 and perhaps it may prolong to another year or more. The covid 19 has curved the normal routine of everyone in the society including the deceased. The school children have to adapt to the new learning style where physical attendance in a normal class room is no longer a necessity. The online learning is now the new mode of study to almost all school children in Malaysia including the university students. Modern technology including smart phones, lap tops and computers are a must have gadgets in every house hold in Malaysia. Personal hygiene is now the highest importance for every people in the society. This has boosted the economy in the sale of sanitizer, hand glove, and face masks. Nonetheless, the lockdown imposed by the government had caused many people in the society to face a major problem of losing their job. The policy of requiring the close down of factories during lock down had indirectly forced the employer to exercise discretion to reduce number of workers and other industry for example the tourism sector had suffered the most. Besides, the lock down had also caused increased in domestic violence as reported in the daily newspaper. This paper intents to discuss the early traces of covid 19 in Malaysia, the new scenario taken place in Malaysia following the spread of Covid 19 in September 2019 to present. The study is made based on the actual scenario in Malaysia, latest update in the local news, observations, and analysis of online materials.